The relationship between duration and quality of sleep and upper respiratory tract infections: a systematic review. (17th May 2021) - Robinson, Charlotte H; Albury, Charlotte; McCartney, David; Fletcher, Benjamin; Roberts, Nia; Jury, Imogen; Lee, Joseph
Abstract: Background: Upper respiratory tract infections (URTIs) are common, mostly self-limiting, but result in inappropriate antibiotic prescriptions. Poor sleep is cited as a factor predisposing to URTIs, but the evidence is unclear. Objective: To systematically review whether sleep duration and quality influence the frequency and duration of URTIs. Methods: Three databases and bibliographies of included papers were searched for studies assessing associations between sleep duration or quality and URTIs. We performed dual title and abstract selection, discussed full-text exclusion decisions and completed 50% of data extraction in duplicate. The Newcastle–Ottawa Quality Assessment Scale assessed study quality and we estimated odds ratios (ORs) using random effects meta-analysis. Results: Searches identified 5146 papers. Eleven met inclusion criteria, with nine included in meta-analyses: four good, two fair and five poor for risk of bias. Compared to study defined 'normal' sleep duration, shorter sleep was associated with increased URTIs (OR: 1.30, 95% confidence interval [CI]: 1.19–1.42, I 2 : 11%, P < 0.001) and longer sleep was not significantly associated (OR: 1.11 95% CI: 0.99–1.23, I 2 : 0%, P = 0.070). Sensitivity analyses using a 7- to 9-hour baseline found that sleeping shorter than 7–9 hours was associated with increased URTIs (OR: 1.31, 95% CI: 1.22–1.41, I 2 : 0%, P < 0.001). Sleeping longer than 7–9 hours was non-significantly associated with increased URTIs (OR: 1.15, 95% CI: 1.00–1.33, I 2 : 0%, P = 0.050, respectively). We were unable to pool sleep quality studies. No studies reported on sleep duration and URTI severity or duration. Conclusions: Reduced sleep, particularly shorter than 7–9 hours, is associated with increased URTIs. Strategies improving sleep should be explored to prevent URTIs. Lay Summary: It is widely believed that poor sleep increases people's chances of catching coughs, colds and other upper airway infections. UK government advice states that poor sleep and catching a cold or the flu could be related and suggests most individuals need 8 hours sleep a night. Studies have helped to explain the link between sleep and infections by showing that shortened sleep reduces the body's ability to fight infections. Studies in humans that look at the link between sleep and catching a cold or other airway infection have mostly been small and have conclusions that differ. We set out to investigate whether the quality of sleep (how 'well' you sleep) and the quantity of sleep (how 'long' you sleep) influence a person's likelihood of getting an upper airway infection. We found that shorter sleep than normal resulted in increased chances of having an upper airway infection, whereas longer sleep did not. We also found that sleeping for shorter or longer than 7–9 hours per night increased the likelihood of having an upper airway infection. Our results are important for informing conversations between patients and doctors around sleep and for encouraging the investigation of the impact of sleep on more serious infections.